HUBUNGAN ANTARA SIKAP TOLERANSI DAN PEMAHAMAN SEJARAH PERGERAKAN NASIONAL DENGAN PATRIOTISME SISWA - Ramadhani, Muhamad Hisyam; Musadad, Akhmad Arif; Pelu, Musa (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2018)
The objectives of research were to find out: 1) the relationship between the attitude of tolerance with patriotism students. 2) The relationship between understanding of national movement history with patriotism students. 3) The relationship between the attitude of tolerance and understanding of national movement history with patriotism students. The population of research was all of the XI grades of SMA Islam 1 Surakarta of academic year 2016/2017, consisting of 68 students. The sample used is of 40 students. The sample was taken using random sampling technique. The technique of collecting data used were questionnaire. The technique of analyzing data used was a multiple linear regression analysis, t-test, multiple correlation analysis (F-test), R2, and relative and effective contribution. The conclusion of research were as: 1) there was a positive relationship between the attitude of tolerance with patriotism students. It could be seen from the multiple linear regression analysis (t-test) the showing that tstatistic > ttable, that is 3,197 > 1,687 and the significance value of 0,03 < 0,05. 2) There was a positive relationship between understanding of national movement history with patriotism. It could be seen from the multiple linear regression analysis (t-test) the showing that tstatistic > ttable, that is 2,653 > 1,687 and the significance value of 0,012 < 0,05. 3) There was a positive relationship between the attitude of tolerance and understanding of national movement history with patriotism students. It could be seen from the multiple correlation analysis (F-test) the showing that Fstatistic > Ftable, that is 15,200 > 3,270 and the significance value < 0,05, of 0,000.